Violence and Pregnancy in G.A. Bredero’s Griane - Poniatowska, Patrycja (Department of Dutch and South African Studies, Faculty of English, 2011)
The eponymous character of Griane, a tragicomedy by G.A. Bredero, is dramatised as a figure of self-produced humoral outrage, which culminates in her becoming pregnant out of wedlock and potentially unsettling political and familial structures. Griane’s pregnancy is staged as an ultimate manifestation of, a consequence of and a punishment for her volatility repeatedly rendered in the drama in evocations of bodily anarchy and/or wounding. Whereas Griane is produced as a quintessence of wilful and unlicensed violence located in the unruly female body and threatening to disrupt both her and the order of the state, the institutional violence of war, execution and incarceration authorised and implemented by the superior male agency is construed in the play as clarifying and restorative. Exposed to such forms of organised violence, Griane internalises the lesson of the postulated feminine submission and is produced as a docile subject. At the same time, the institutional and political dimension of punitive violence is obscured by insistence on the secrecy and privacy of Griane’s predicament.
Keywords: body; gender; humours; incarceration; patriarchy; punishment; pregnancy; Renaissance drama; violence